Efficient nitrite determination by electrochemical approach in liquid phase with ultrasonically prepared gold-nanoparticle-conjugated conducting polymer nanocomposites - Faisal, M.; Alam, M. M.; Ahmed, Jahir; Asiri, Abdullah M.; Algethami, Jari S.; Altholami, Raed H.; Harraz, Farid A.; Rahman, Mohammed M. (Frontiers in Chemistry, 2024)
In this approach, an electrochemical nitrite sensor probe was introduced by using a modified flat glassy carbon electrode (GCE) with spherical shaped gold nanoparticles (Au-NPs) decorated SrTiO3 doped material, polypyrrole-carbon (Au-NPs/PPyC/SrTiO3 NCs) at pH of 7.0 in phosphate buffer solution (PBS). Nanocomposites (NCs) of Au-NPs, PPyC, and SrTiO3 were synthesized by ultrasonication. Later NCs properties were also thoroughly characterized by using structural, elemental, optical and morphological analysis with various conventional spectroscopic methods including powder FESEM, EDS, HR-TEM, XRD, XPS, BET etc. Peak currents due to nitrite oxidation were characterized in details and analyzed by using conventional cyclic voltammetry (CV) as well as differential pulse voltammetry (DPV) in a room conditions. The sensor response increased significantly from 0.15 to 1.5 mM of nitrite ion, which was fabricated with conducting coating agent (PEDOT:PSS) onto GCE as Au-NPs/PPyC/SrTiO3 NCs/PEDOT:PSS/GCE probe. The sensor's sensitivity was determined as 0.5 µA.µM -1 .cm -2 from the ratio of the slope of the linear detection range (LDR) by considering the active surface area (0.0316 cm 2 ) of flat-GCE. In addition, the LOD was determined as 20.00±1.00 µM, which is found satisfactory results. The sensor's stability, pH optimization, and reliability were also evaluated in these analyses. The overall sensor results were found to be good and satisfactory. Real environmental samples were analyzed to test the sensor's reliability by DPV. The results showed that this novel electrochemical sensor has great potential for mitigating water contamination in the real collected samples with lab-made nanocomposite of Au-NPs/PPyC/SrTiO3. This study provides the valuable insights for improving electrochemical sensors for environmental monitoring applications in a broad scale using electrochemical approach.